The China Syndrome: Local Labor Market Effects of Import Competition in the United States - Autor, David H; Dorn, David; Hanson, Gordon H (American Economic Review, 2013)
We analyze the effect of rising Chinese import competition between 1990 and 2007 on US local labor markets, exploiting cross-market variation in import exposure stemming from initial differences in industry specialization and instrumenting for US imports using changes in Chinese imports by other high-income countries. Rising imports cause higher unemployment, lower labor force participation, and reduced wages in local labor markets that house import-competing manufacturing industries. In our main specification, import competition explains one-quarter of the contemporaneous aggregate decline in US manufacturing employment. Transfer benefits payments for unemployment, disability, retirement, and healthcare also rise sharply in more trade-exposed labor markets. (JEL E24, F14, F16, J23, J31, L60, O47, R12, R23)